2022
DOI: 10.1111/desc.13245
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of inhibitory control and associations with cognitive outcomes in Bangladeshi children exposed to early adversities

Abstract: There is strong support for the view that children growing up in low‐income homes typically evince poorer performance on tests of inhibitory control compared to those growing up in higher income homes. Unfortunately, the vast majority of the work documenting this association has been conducted in high‐income countries. It is not yet known whether the mechanisms found to mediate this association would generalize to children in low‐ and middle‐income countries, where the risks of exposure to extreme poverty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 91 publications
2
10
1
Order By: Relevance
“…About the ERPs in the Go/No-go task at 5 years of age, in consonance with the literature, the N2 and P3 were more pronounced in the No-go than in the Go condition (Lahat, 2010;Abdul Rahman et al, 2017;Sullivan et al, 2022). Unlike other studies (Sullivan et al, 2022), no differences in peak latency were found for N2 or P3 components. Only the difference peak amplitude in the N2 component was concurrently correlated with behavioral indicators of IC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…About the ERPs in the Go/No-go task at 5 years of age, in consonance with the literature, the N2 and P3 were more pronounced in the No-go than in the Go condition (Lahat, 2010;Abdul Rahman et al, 2017;Sullivan et al, 2022). Unlike other studies (Sullivan et al, 2022), no differences in peak latency were found for N2 or P3 components. Only the difference peak amplitude in the N2 component was concurrently correlated with behavioral indicators of IC.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the correlation of N2 and P3 amplitudes with behavioral measures in the Go/No-go task is not always found in the literature regarding the pediatric population (Jonkman et al, 2003). For example, a recent study found that N2 difference peak amplitude was uncorrelated to performance in 5-year-olds (Sullivan et al, 2022). This discrepancy in the results could be explained by the fact that in this study, a general accuracy measure was used instead of focusing on more specific measures of IC (such as accuracy in No-go trials or d').…”
Section: Discussionmentioning
confidence: 98%
“…A fourth group of articles looked more closely at the environmental factors and experiences that influence executive function performance. Sullivan et al (2022) observed that behavioral and ERP markers of inhibitory control were all associated with the IQ scores, and 5-yearolds children who experienced higher levels of psychosocial adversity had a lower accuracy of the task and lower IQ scores. Stucke et al (2022) examined home activities during the COVID-19 pandemic and time and variety of less-structured activities (wide range of activities permitting choice and interaction with caregiver) were related to successful switching on the Dimensional Change Card Sort at preschool age, controlling for age, family income, caregiver education, and verbal knowledge.…”
mentioning
confidence: 96%
“…Sullivan et al. (2022) observed that behavioral and ERP markers of inhibitory control were all associated with the IQ scores, and 5‐year‐olds children who experienced higher levels of psychosocial adversity had a lower accuracy of the task and lower IQ scores. Stucke et al.…”
mentioning
confidence: 99%
“…This association may also include lower white matter that supports EFs (e.g., Ursache & Noble, 2016;Rosen et al, 2018;age range: 3-21 years). On the other hand, studies that investigated disparities in brain function in tasks with EF demands indicated that low SES during childhood may be associated with modifications in the activation of the frontoparietal network, prefrontal cortex, and electrophysiological patterns in frontocentral scalp regions during the performance of tasks that demanded response inhibition (Brooker, 2018;John et al, 2019;Sullivan et al, 2022;Tomlinson et al, 2020; age range: 3-18 years) working memory (Rosen et al, 2018;Sheridan et al, 2017;age range: 11-20 years), control information interference (D'Angiulli et al, 2008(D'Angiulli et al, , 2012Giuliano et al, 2018;Isbell et al, 2016;Stevens et al, 2009;Wray et al, 2017;age range: 3-8 years), and detection of a perceptual conflict or novelty (Conejero et al, 2018;Kishiyama et al, 2009;age range: 2-12 years). The evidence from resting-state studies indicated that childhoods with low SES may be associated with modification in the power of different brain oscillations on frontal scalp regions (Harmony et al, 1990;Otero et al, 2003;Tomalski et al, 2013;age range: 6 months-12 years).…”
mentioning
confidence: 99%